SUPPLY CHAIN STRATEGIES AND THEIR REFLECTION ON SALES PROMOTION (A field study in Misan Company for the Production of Dairy and Refreshments Ltd.) (American Journal of Business Management, Economics and Banking, 2023)
This work aims to identify supply chain strategies and their reflection on sales promotion in Misan Dairy and Refreshments Co. Ltd.A questionnaire was developed to ensure a relationship between the research variables, and based on the comprehensive inventory method, (89) questionnaires were distributed in Misan Company for Dairy and Beverages Production Ltd., and their data was analyzed using (SPSS V.24) program.